Two new endemic species of Lygaeinae from Baja California, Mexico (Hemiptera: Heteroptera: Lygaeidae) - Peredo, Luis Cervantes; Brailovsky, Harry (Zootaxa, 2014)
Two new species of Lygaeinae endemic to the Peninsula of Baja California, Mexico, are described. Dalmochrimnus insularis sp. nov. endemic to San Ildefonso Island in the Gulf of California and Melacoryphus lagunensis sp. nov. endemic to the Reserve area of Sierra La Laguna in the South of the Peninsula. A discussion about their relationships within their genera and their endemic status is also provided.